The role of the community mental health nurse in Botswana: The needs and problems of carers of schizophrenic clients in the community - A. Kgosidintsi (AOSIS, 1996)
The purpose of this study was to identify and describe the role of the psychiatric/community mental health nurse in the context of primary health care in which mental health is an integral part of the general health care system and in a specific socio-economic background. Nine (9) community mental health nurses who graduated from a local training program for community mental health nurses at post basic level, twenty five (25) carers responsible for daily care and welfare of schizophrenic clients from rural, semi-rural, urban and semi-urban areas country wide participated in the study. The study was exploratory and both qualitative and quantitative data was collected using semi structured interviews, unstructured observation and documentary search methods were used. Data analysis for both qualitative and quantitative data was done through simple frequency counts.